2011
DOI: 10.1111/j.1574-695x.2011.00802.x
|View full text |Cite
|
Sign up to set email alerts
|

A highly immunogenic recombinant and truncated protein of the secreted aspartic proteases family (rSap2t) ofCandida albicansas a mucosal anticandidal vaccine

Abstract: Sap2 (secreted aspartyl proteinase2) is a member of the Sap family of Candida albicans, a human opportunistic pathogen, which acts as a virulence factor in experimental animal models of mucosal candidiasis. The C. albicans SAP2 was subcloned into vector pDS56-RBSII-6xhis, under the control of an inducible promoter to produce a truncated 6xhis-tagged, enzymatically inactive Sap2, lacking the N-terminus 76 amino acids (rSap2t). This recombinant protein was purified to homogeneity by one-step nickel-chelate affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 41 publications
(74 reference statements)
4
52
0
1
Order By: Relevance
“…Expression of Sap proteases may contribute to the pathology of these superficial infections via activation of the inflammasome. This hypothesis is supported by the fact that expression of SAP genes and Sap antigens, including Sap2 and Sap6, is frequently detected during vaginal infection [15,52], and that antibodies against Sap2 have been shown to be protective against C. albicans challenges in a rat vaginal infection model [56,57]. Differences in the magnitude and mechanisms of induction are also likely, as in part suggested by some differences shown here between Sap2 and Sap6 in the kinetics of caspase-1 activation.…”
supporting
confidence: 51%
“…Expression of Sap proteases may contribute to the pathology of these superficial infections via activation of the inflammasome. This hypothesis is supported by the fact that expression of SAP genes and Sap antigens, including Sap2 and Sap6, is frequently detected during vaginal infection [15,52], and that antibodies against Sap2 have been shown to be protective against C. albicans challenges in a rat vaginal infection model [56,57]. Differences in the magnitude and mechanisms of induction are also likely, as in part suggested by some differences shown here between Sap2 and Sap6 in the kinetics of caspase-1 activation.…”
supporting
confidence: 51%
“…121 Rats receiving intravaginal immunisation with amino acids 77-400 of Sap2p were protected against subsequent vaginal challenge with C. albicans in a manner dependent upon the generation of anti-Sap2p IgG and IgA. 122 As well as virulence factor vaccines, other formulations have been designed based on structural motifs. A vaccine containing the algal b-glucan laminarin has been reported to improve immune protection against 123 both vaginal (mucosal) and systemic C.…”
mentioning
confidence: 99%
“…Several studies have reported the search for new vaccines (Devi et al, 1991;Han et al, 1999;Segal, 1999;Stevens et al, 2000;Casadevall and Pirofski, 2001;Torosantucci et al, 2005;Spellberg et al, 2008;Liu and Filler, 2011;Sandini et al, 2011;Cassone and Casadevall, 2012), particularly against cryptococcosis, histoplasmosis (Georgopapadakou and Walsh, 1996;Chaturvedi and Wormley, 2013) coccidioidomycosis, blastomycosis and candidiasis (Segal, 1999;Barnato et al, 2001;Walsh, 2002;Cassone and Casadevall, 2012). Polysaccharide-protein conjugate vaccines were shown to be effective against Cryptococcus neoformans (Devi et al, 1991) and Candida albicans (Han et al, 1999).…”
Section: Different Approaches and Different Alternative Sourcesmentioning
confidence: 99%